TREND SUBSEKTOR KEHUTANAN TERHADAP PDRB, KESEMPATAN KERJA DAN EKSPOR PULANG PISAU PROVINSI KALIMANTAN TENGAH: Trends of The Forestry Subsector on GRDP, Employment Opportunities and Exports of Pulang Pisau District Kalimantan Tengah Province - Putra Agustinus Simarmata; Jumri Dulamin; M. Damiri (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2020)
This study is to analyze the magnitude of forestry subsector trends on the economy,especially on Gross Regional Domestic Revenue, Job Opportunities and Pulang PisauTotal Value. This study uses secondary data and is analyzed by Straight Line Equations.Research results obtained: 1. The contribution of the forestry sub-sector to the PulangPisau Regency economy began to decline in 2010-2018. Where the highest contributionwas in 2010 which was 2.27% with a value of Rp 43,927.30 while the lowest contributionvalue was in 2018 which was 1,44% with a value of Rp 70.494,50 with an averagegrowth of -5.45%. 2. The participation rate of Pulang Pisau Regency's employmentopportunities from 2010-2018 tends to decrease. For the highest contribution, there were73,12% in 2010, while the lowest contribution was in 2017 with a value of 46% with anaverage growth of 4,78%. 3. The Total Value of Forestry Subsector Exports in 2015-2019 increased from year to year from the analysis of the total value of total forestryexports in 2015-2019, the highest value was in 2018, namely USD 6,473,834.63 whilethe lowest was in 2015, which was USD 58,679 60Keywords: Gross Regional Domestic Revenue, Labor, Total Export Value